Comparative analysis of HIV cases in Latin America (Research, Society and Development, 2022)
The Human Immunodeficiency Virus (HIV) infection is considered a worldwide pandemic and efforts have been made to mitigate this problem. The Joint United Nations Program on HIV/AIDS (UNAIDS) proposes strategies and goals in HIV interventions. Thus, this study aimed to analyze data on HIV in Latin American countries so they can be used to improve the quality of life of people living with HIV and guide the of public policies. This is an ecological observational analytical study. Data was obtained from the World Health Organization (WHO) website by the Global Health Observatory (GHO) repository. The variables analyzed were: “Number of new HIV infections”, “Number of deaths from HIV/AIDS”, “Prevalence of HIV among adults aged 15 to 49 years”, “Estimated number of people of all ages living with HIV”, “Number of people receiving antiretroviral therapy”, “Antiretroviral therapy coverage (%)” and “New HIV infections (per 1,000 uninfected population)”. Given these variables, the results showed that most Latin American countries presented an increase in new cases between 2010 a 2020, with a decline or stability in deaths from the disease in all countries. Regarding the coverage of antiretroviral therapy, all Latin American countries are far from the UNAIDS target. It is hoped that health surveillance, managers and health professionals in Latin American countries can use the results found. Therefore, it is possible to verify the failures and successes of public policies resulting in benefits for the community.